Pengembangan Perangkat Pembelajaran Bahasa Indonesia Berbasis Problem Posing pada Materi Debat Siswa Kelas X SMA Negeri 1 Delitua - Rosmawati Putri (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2021)
Problem possing is a learning model that requires students to compose their own questions or break a question into simpler questions that refer to solving the problem. The purpose of this study was to develop a valid, practical, and effective problem posing-based learning tool for debate material for class X SMA Negeri 1 Delitua consisting of Student Worksheets (LKPD) and Learning Implementation Plans (RPP). This development model uses a development model adapted from Sugiyono's level 1 research. The sample or respondents of this study were Indonesian teachers at SMA Negeri 1 Delitua which consisted of 6 teachers. The results of data analysis can be concluded that the learning tools developed are categorized as valid, practical, and effective with the level of validity of the Student Worksheet (LKPD) tested by 2 material experts is 95.2% and 85.6%. Meanwhile, the lesson plan (RPP) is 85.2% and 88%. Thus, it can be concluded that the problem posing-based learning tool developed is feasible to use.